Strain-induced polarization in non-centrosymmetric bulk 3R-MoS2 for enhanced piezocatalytic persulfate activation: Performance and mechanistic insights - Chunyang Nie; Zesheng Hu; Yuehan Wang; Shiting Li; Xiaoxiao Fu; Zhimin Ao; Changqing Sun (Journal of Environmental Chemical Engineering, 2026)

Plant diversity drives grassland restoration by enhancing belowground ecosystem multifunctionality - Meili He; Chunyang Fu; Mei Hua; Wanjie Chen; Lingling Chen (Agriculture, Ecosystems & Environment, 2026)

Mixed-dimensional COF membrane towards fast organic solvent nanofiltration - Fenglong Dai; Tingyuan Wang; Yanan Liu; Xiaocui Wei; Fu Zhao; Enshen Shi; Yigui Du; Chunjia Wang; Shijie Liu; Chunyang Fan; Yuhan Wang; Zhongyi Jiang (Chemical Engineering Journal, 2026)

Interfacial hydrogen bonding as a key driver for selective phenolic compounds removal via Mg(OH)2-catalyzed peroxymonosulfate activation - Yuan Ding; Jiachun Cao; Shiting Li; Hong Huang; Honggen Peng; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2026)

A few-shot fault diagnosis method for ship motors based on multi-source data and multi-view task guidance - Yuan Xu; Deqiang He; Chunyang Dai; Zhenzhen Jin; Yanjun Chen; Yang Fu (Ocean Engineering, 2026)

Inhibition and metabolic toxicity regulation of niacin on Staphylococcus aureus and its application in meat product preservation - Lei Tian; Xiangqi Bai; Chunyang Huang; Min Li; Ting Zhou; Chunling Zhang; Ying Yu; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

5-Aza-CdR increases expression of the tight junction protein ZO-1 via upregulation of miR-126 through promoter hypomethylation in HMEC-1 cells - Xi Zhang; Shaohan Zhang; Yuzhi Shao; You Liu; Kerui Gong; Chunyang Zhang; Zhijun Zhao; Xuguo Ma; Gang Fu; Guo Shao (Tissue and Cell, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

A neighborhood effect-based method for urban wind environment assessment and regulation - Xiaoqin Liu; Shuliang Zhao; Xiang Huang; Yuqing Ma; Chunyang Zhu; Zongchi Fu (Building and Environment, 2026)

Antibacterial mechanism of vitamin C against Staphylococcus aureus, reduction of toxicity of metabolites and its application in pasteurized milk - Lei Tian; Chunyang Huang; Xing Liu; Yuxin Zhang; Ting Zhou; Ying Yu; Chunling Zhang; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

Inflammation-related lncRNAs in the regulation of kidney injuries; special emphasis on novel lncRNA-based delivery platforms - Xu Fu; Rawaa Najim Alkhamessi; Raed Fanoukh Aboqader Al-Aouadi; Mustafa Jawad Kadham; Surayyo Khasanova; Mana Shree; Pushkar Jassal; Aashna Sinha; Natrayan Lakshmaiya; ChunYang Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A comparative study on catalytic activation of peroxymonosulfate over polytype 2H-MoS2 and 3R-MoS2 - Shiting Li; Yuehan Wang; Chang Cai; Hong Huang; Honggen Peng; Xiaoxiao Fu; Zhimin Ao; Chunyang Nie (Journal of Environmental Chemical Engineering, 2025)

Significantly enhanced piezo-photocatalytic in-situ H2O2 generation and activation for efficient antibiotic degradation by g-C3N4/NH2-MIL-101(Fe) heterojunction - Yao Zhang; Yong Jiang; Wenbo Fu; Chunyang Zhai; Jing Guo (Journal of Environmental Chemical Engineering, 2025)

Activating graphitic carbon via a core/shell WO3/carbon architecture for electrocatalytic deactivation of dilute antibiotics - Wenyang Fu; Yanjun Yin; Jiahong Zou; Chunyang Dan; Shenbin Zheng; Huimin Sui; Yinan Liu; Yan Zou; Heng Shi; Guangming Jiang (Chemical Engineering Journal, 2025)

Insight into the piezo-activation of peroxymonosulfate by 1T/2H-MoS2: piezopotential boosting the formation of Mo-peroxymonosulfate complexes as the major reactive species - Tian Jiang; Chang Cai; Honggen Peng; Jianjun Li; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2025)

Sustainable peroxymonosulfate activation by 1T/2H-MoS2 cathode for enhanced removal of organic pollutants: Performance and nonradical activation mechanism based on surface Mo-peroxymonosulfate complexes - Chang Cai; Tian Jiang; Honggen Peng; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2025)

Pressure-induced formation of porous g-C₃N₅ for efficient photocatalytic degradation of tetracycline (TC) - Tingting Ma; Yao Zhang; Yuhang Tian; Wenbo Fu; Yong Jiang; Chunyang Zhai (Journal of Environmental Chemical Engineering, 2025)

Cyclodextrin tuned interlayer spacing in covalent organic framework membranes for efficient dye/salt separation - Xiaocui Wei; Yanan Liu; Jianghao Huang; Zongmei Li; Fu Zhao; Zhao Zhang; Tingyuan Wang; Chunyang Fan; Yuhan Yang; Zhongyi Jiang (Desalination, 2025)

Occurrence and migration of synthetic phenolic antioxidants in food packaging materials: Effects of plastic types and storage temperature - Yexi Yin; Jiayi Zhou; Huiyang Fu; Shuang Liu; Qingqing Zhu; Chunyang Liao; Guibin Jiang (Science of The Total Environment, 2025)

LcMYB5, an R2R3-MYB family gene from Lonicera caerulea L., enhances drought and salt tolerance in transgenic tobacco and blue honeysuckle - Chunlin Fu; Chunyang Bian; Jing Chen; Qian Zhang; Dong Qin; Jiangkuo Li; Peng Zhang; Junwei Huo; Huixin Gang (Journal of Plant Physiology, 2025)

Up-regulation of miR-126 via DNA methylation in hypoxia-preconditioned endothelial cells may contribute to hypoxic tolerance of neuronal cells - Pu Zhang; Gang Fu; Wenqing Xu; Kerui Gong; Zhujun Zhao; Kai Sun; Chunyang Zhang; Ruijuan Han; Guo Shao (Molecular Biology Reports, 2024)

A preliminary understanding of the relationship between synthetic phenolic antioxidants and early pregnancy loss: Uncovering the potential molecular mechanisms - Yaqian Xu; Na Zhang; Yu Hu; Fu Chen; Ligang Hu; Chunyang Liao; Guibin Jiang (Science of The Total Environment, 2024)

Bioleaching of Cd from contaminated Helianthus annuus L. stalk and the safe utilization of its byproducts by Aspergillus niger - Qiuguo Zhang; Dongsheng Zou; Xinyi Zeng; Yang Yang; Chunyang Zeng; Mingming Li; Zhaolong Fu; Qingru Zeng (Environmental Research, 2024)

Comprehensive analysis of MAPK gene family in upland cotton (Gossypium hirsutum) and functional characterization of GhMPK31 in regulating defense response to insect infestation - Fuqiu Wang; Sijia Liang; Guanying Wang; Qiongqiong Wang; Zhongping Xu; Bo Li; Chunyang Fu; Yibo Fan; Tianyu Hu; Muna Alariqi; Amjad Hussain; Jinglin Cao; et al. (Plant Cell Reports, 2024)
Key message The transcriptomic, phenotypic and metabolomic analysis of transgenic plants overexpressing GhMPK31 in upland cotton revealed the regulation of H 2 O 2 burst and the synthesis of defensive metabolites by GhMPK31 . Abstract Mitogen-activated protein kinases (MAPKs) are a crucial class of protein kinases, which play an essential role in various biological processes in plants. Upland cotton ( G. hirsutum ) is the most widely cultivated cotton species with high economic value. To gain a better understanding of the role of the MAPK gene family, we conducted a comprehensive analysis of the MAPK gene family in cotton. In this study, a total of 55 GhMPK genes were identified from the whole genome of G. hirsutum . Through an investigation of the expression patterns under diverse stress conditions, we discovered that the majority of GhMPK family members demonstrated robust responses to abiotic stress, pathogen stress and pest stress. Furthermore, the overexpression of GhMPK31 in cotton leaves led to a hypersensitive response (HR)-like cell death phenotype and impaired the defense capability of cotton against herbivorous insects. Transcriptome and metabolomics data analysis showed that overexpression of GhMPK31 enhanced the expression of H 2 O 2 -related genes and reduced the accumulation of defensive related metabolites. The direct evidence of GhMPK31 interacting with GhRBOHB (H 2 O 2 -generating protein) were found by Y2H, BiFC, and LCI. Therefore, we propose that the increase of H 2 O 2 content caused by overexpression of GhMPK31 resulted in HR-like cell death in cotton leaves while reducing the accumulation of defensive metabolites, ultimately leading to a decrease in the defense ability of cotton against herbivorous insects. This study provides valuable insights into the function of MAPK genes in plant resistance to herbivorous insects.

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

BCE-Net: Reliable building footprints change extraction based on historical map and up-to-date images using contrastive learning - Cheng Liao; Han Hu; Xuekun Yuan; Haifeng Li; Chao Liu; Chunyang Liu; Gui Fu; Yulin Ding; Qing Zhu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Ginsenoside Biosynthesis in Panax Ginseng with Red-Skin Disease Is Inhibited by Soil Characteristics - Rui Ma; Baoyu Fu; Shikuan Song; Chunyang Zhang; Xiajun Yuan; Tingshi Zhang; Daqing Zhao; Liwei Sun (Journal of Soil Science and Plant Nutrition, 2021)

In-flight transmission cluster of COVID-19: a retrospective case series - Naibin Yang; Yuefei Shen; Chunwei Shi; Ada Hoi Yan Ma; Xie Zhang; Xiaomin Jian; Liping Wang; Jiejun Shi; Chunyang Wu; Guoxiang Li; Yuan Fu; Keyin Wang; et al. (Infectious Diseases, 2020)

Stoichiometric flexibility and soil bacterial communities respond to nitrogen fertilization and neighbor competition at the early stage of primary succession - Mengya Song; Lei Yu; Shenglei Fu; Helena Korpelainen; Chunyang Li (Biology and Fertility of Soils, 2020)

Depression in older patients with advanced colorectal cancer is closely connected with immunosuppressive acidic protein - Rong Li; Jie Yang; Jihua Yang; Weijun Fu; Hua Jiang; Juan Du; Chunyang Zhang; Hao Xi; Jian Hou (Metabolic Brain Disease, 2014)

Polycyclic aromatic hydrocarbons and organochlorine pesticides in rice hull from a typical e-waste recycling area in southeast China: temporal trend, source, and exposure assessment - Fang Liu; Chunyang Liao; Jianjie Fu; Jungang Lv; Qinzhao Xue; Guibin Jiang (Environmental Geochemistry and Health, 2014)